ANALISIS PENERAPAN PENYAJIAN LAPORAN KEUANGAN ZAKAT BERDASARKAN PSAK 109 (Studi Kasus Baitul Mal Aceh Utara Dan Baitul Mal Lhokseumawe) - Zulkarnaini Zulkarnaini; Muhammad Arifai; M. Nasir; Marjuliati Harahap (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
This research is entitled Analysis of Application of Zakat Financial Statement Presentation Based on Statement of Financial Accounting Standards 109 (Case Study of Baitul Mal Aceh Utara and Baitul Mal Lhokseumawe). This study aims to determine whether the financial statements are in accordance with zakat accounting reporting, namely recognition, measurement, presentation/reporting, and disclosure at Baitul Mal Aceh Utara and Baitul Mal Lhokseumawe. This research is located at Jl. New Ocean No. 53, Kampung Jawa, Banda Sakti, Lhokseumawe City, Aceh. And at the Lhokseumawe City Islamic Center Complex. The method used in this research is descriptive quantitative research method. Data analysis was carried out in this study using confirmatory factor analysis with data collection techniques in this study, namely by using interviews, questionnaires, literature studies. The population in this study is the target population with the number of respondents as many as 60 (sixty) people (30 (thirty) people at Biatul Mal Aceh Utara and 30 (thirty) people at Baitul Mal Lhokseumawe). The results of this study indicate that the recognition of the Statement of Financial Accounting Standards 109 on zakat accounting reporting at Baitul Mal Aceh Utara and Baitul Mal Lhokseumawe has been implemented properly. Keywords : Financial Accounting Report, Baitul Mal, Statement of Financial Accounting Standards 109